Performance of Goat Production Supply Chain Models and Institutions in South Sulawesi, Indonesia - Hastang, Hastang; Baba, Syahdar; Asnawi, Aslina; Andi Dagong, Muhammad Ihsan; Sirajuddin, Sitti Nurani (International Journal of Supply Chain Management, 2020)
Abstract This study examines the model for the goat production supply chain and institution performance in the supply chain from production centers (Jeneponto Regency) to consumption centers (Makassar City). The institutions discussed here are only institutions that are included in the chain as primary members. The performance of goat supply chain institutions can be seen from the benefits obtained in the highest order, namely breeders, retailers, and collectors in Channel 1, while in Channel 2, they are farmers, intermediary consumers, collectors and retailers. The profit gained breeders from marketing margins in both channels is quite good; the respective values are 67.43% and 64.66% of total marketing margins.